Surgical ciliated cyst after a mandibular surgery: a particular case report and review of the literature - Irene Lafuente-Ibáñez de Mendoza; Marta Fernández-Reyes; Antonio Fernández-Arenas; José Manuel Aguirre-Urizar (BMC, 2021)
Abstract Background Surgical ciliated cyst is a rare clinicopathological lesion that appears in patients who undergo maxillofacial surgery. In this report we present a particular mandibular case and we discuss the etiopathogenesis and clinicopathological features of this pathology after reviewing the current literature, as well as the origin of its respiratory epithelial profile. Case presentation The patient is a 67-year-old male with an irregular radiolucency in a previously tooth extracted area of the mandible. The histopathological study revealed a cystic lesion with a connective wall with chronic inflammation, partially lined by a ciliated pseudostratified epithelium. PAS and CK19 stains showed the respiratory characteristics of this epithelium and confirmed the final diagnosis of mandibular surgical ciliated cyst. Conclusions Surgical ciliated cyst is an uncommon entity associated with maxillofacial surgical procedures with bone and nasal cartilage grafts. In our case, treatment with growth factors present in platelet-rich plasma could explain the respiratory changes observed in the cystic epithelial lining."